CORRELATION OF WORKING CONDITION AND JOB COMMITMENT AMONG VETERINARIANS IN KERALA - Soumya Sankar and Reeja George P. (International Journal of Research in Social Sciences, 2013)
The present study reveals the correlation between working condition and job commitment of veterinarians. The study was conducted among the veterinarians of the Department of Animal Husbandry, Kerala. Data were collected using structured questionnaire among 45 senior veterinary surgeons and 155 veterinary surgeons. Result of study indicated that there was negative and highly significant correlation between stress due to working condition and job commitment. Result also revealed that majority of the respondents had moderate level of stress due to unfavourable working condition. A better understanding of the stressors in veterinary practice may allow identification of strategies to improve the working conditions of veterinarians with resulting benefits for the quality of veterinary health care.